PERBEDAAN MOTIVASI MAHASISWA MENJADI PERAWAT SEBELUM DAN SESUDAH MENJALANI PRAKTEK KLINIK KEPERAWATAN - Wulandari, Rista (Coping: Community of Publishing in Nursing, 2014)
1024x768 Motivation is the drive to do a series of events that lead to the achievement of a particular goal. Factors that affect motivation can come from within or from outside the individual. How strong motivation of the individual will determine the quality of the display behavior, including in the context of learning. This study aimed to determine differences in student motivation to be a nurse before and after undergoing prakek clinical nursing at the Faculty of Medicine Udayana University student PSIK fourth semester, on February 14, 2014 and July 7, 2014 This is a type of pre-experimental research design with the design of one group pretest-posttest design with a sample consisting of 69 students were selected in total sampling. Previously performed a pre-test measurement of motivation before undergoing clinical nursing practice. Post-test was carried out after the implementation of nursing clinical practice. Measurement of motivation pre-test and post-test was performed using a research instrument that uses a Likert scale questionnaire. This questionnaire refers to Maslow's theory of motivation. Results of studies using the Wilcoxon test, significance level of motivation obtained before and after undergoing the nursing clinical practice p = 0.001 (p value ?0,05) which means that there are differences in student motivation to be a nurse before and after undergoing clinical nursing practice. Normal 0 false false false EN-US X-NONE X-NONE /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: motivation; nursing clinical practice; nurses